Occupational therapy and mental health - Creek, Jennifer, ....-; Lougher, Lesley, ....-; van Bruggen, Hanneke, ....- (Edinburgh : Churchill Livingstone, 2008)
The book is a comprehensive textbook for occupational therapy students and occupational therapists working in the field of mental health. It presents different theories and approaches used, outlines the occupational therapy process, discusses the context of practice, and describes a wide range of techniques used by occupational therapists. These include physical activity, cognitive approaches, group work, creative activities, play and life skills. The book covers all areas of practice in the field, including mental health promotion, acute psychiatry, community work, severe and enduring mental illness, working with older people, child and adolescent mental health, forensic occupational therapy, substance misuse and working with people on the margins of society. The theory chapters are written by occupational therapists who are recognised experts in their fields and the applied chapters are written by practitioners. an innovation in this edition is the inclusion of commentaries by service
Users on some of the chapters. The fourth edition has been extensively revised and updated. The new structure reflects changes in service delivery and includes sections on philosophy and theory base, the occupational therapy process, ensuring quality, the context of occupational therapy, occupations, and client groups. Important new areas that are now covered include mental health promotion, evidence-based practice, community development, and continuing professional development. Table of Contents Foreword by Haneke van Bruggen Preface Section 1 - Philosophy and theory base Chapter 1 - A short history of occupational therapy in psychiatry (Catherine F. Paterson) Chapter 2 - Occupational perspectives on mental health and well-being (Sheena E.E. Blair, Clephane A. Hume, Jennifer Creek) Chapter 3 - The knowledge base of occupational therapy (Jennifer Creek) - Service user commentary Section 2 - The occupational therapy process Chapter 4 - Approaches to practice (Jennifer Creek) - Service user
Commentary Chapter 5 - Assessment and outcome measurement (Jennifer Creek and Alison Bullock) Chapter 6 - Planning and implementation (Jennifer Creek and Alison Bullock) Chapter 7 - Record keeping (Mary Booth) Section 3 - Ensuring quality Chapter 8 - Clinical governance and clinical audit (Clare Beighton) Chapter 9 - Management (Lynne Barr) Chapter 10 - Research, evidence-based practice and professional effectiveness (Irene Ilott) - Service user commentary Section 4 - The context of occupational therapy Chapter 11 - Ethics (Jenny Butler, Jennifer Creek) Chapter 12 - Roles and settings (Cathy Ormston) Chapter 13 - the developing student practitioner (Marion Martin and Sue Wheatley) Chapter 14 - Working in a transcultural context (Kee Hean Lim) Section 5 - Occupations Chapter 15 - Mental health and physical activity: enabling participation (Fiona Cole) Chapter 16 - Cognition and cognitive based approaches in occupational therapy (Edward A.S.Duncan) Chapter 17 - Client centred groups ( Marilyn
B. Cole) Chapter 18 - Creative activities (Jennifer Creek) Chapter 19 - Play (Deborah Hutton) Chapter 20 - Life skills (Mary Roberts) Section 6 - Client groups Chapter 21 - Loss and grief (Clephane A. Hume) Chapter 22 - Acute psychiatry (Robert Hawkes, Valerie Johnstone, Lynn Yarwood) Chapter 23 - Approaches to severe and enduring mental illness (Simon Hughes) Chapter 24 - Older people (Jackie Pool) Chapter 25 - Child and adolescent mental health services (Lesley Lougher, Deborah Hutton, Donna Guest, Alan Evans) Chapter 26 - Learning disabilities (Anne Fleming) Chapter 27 - Community mental health (Jon Fieldhouse) Chapter 28 - Forensic occupational therapy (Edward A.S. Duncan) Chapter 29 - Substance misuse (Jenny Lancaster and John Chacksfield) Chapter 30 - Working with people on the margins (Nick Pollard, Frank Kronenberg) Glossary Index
Keywords: Ergotherapie -- Mentaal gehandicapten; Ergotherapie -- Psychiatrie; Ergotherapie